2021
DOI: 10.1101/2021.04.19.440300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Driver of Blood Circulation Beyond the Heart

Abstract: The heart is widely acknowledged as the unique driver of blood circulation. Recently, we discovered a flow-driving mechanism that can operate without imposed pressure, using infrared (IR) energy to propel flow. We considered the possibility that, by exploiting this mechanism, blood vessels, themselves, could propel flow. We verified the existence of this driving mechanism by using a three-day-old chick-embryo model. When the heart was stopped, blood continued to flow, albeit at a lower velocity. When IR was in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In support of the existence of local temperature-sensitive regulatory mechanisms, a recent study utilising a 3-day-old chick embryo model revealed that after the heart has been arrested with KCl, blood velocity in the vitelline vessel still increased ∼ 3.7-fold in response to infrared radiation (heat energy) but ceased completely when the heat source was taken away. Hence, the present data together with previous observations in the literature (Manteuffel-Szoege, 1960, 1969 indicate that a heat-dependent mechanism can operate in the circulatory system (Li & Pollack, 2023).…”
Section: Interaction Among Heating Modalities and Tissue Temperature ...supporting
confidence: 87%
“…In support of the existence of local temperature-sensitive regulatory mechanisms, a recent study utilising a 3-day-old chick embryo model revealed that after the heart has been arrested with KCl, blood velocity in the vitelline vessel still increased ∼ 3.7-fold in response to infrared radiation (heat energy) but ceased completely when the heat source was taken away. Hence, the present data together with previous observations in the literature (Manteuffel-Szoege, 1960, 1969 indicate that a heat-dependent mechanism can operate in the circulatory system (Li & Pollack, 2023).…”
Section: Interaction Among Heating Modalities and Tissue Temperature ...supporting
confidence: 87%
“…The study also revealed that, on an intact chick embryo, blood failed to flow when the heat source that maintained a physiological body temperature was taken away. A heat‐dependent, vessel‐based flow‐driving mechanism could therefore operate in the circulatory system (Li & Pollack, 2023; Manteuffel‐Szoege, 1960, 1969), working in synergy with the heart and the neurohumoral systems to increase flow and maintain the arterio‐venous pressure gradients as generally observed in the present passive hyperthermia conditions. The observations in ex vivo pressurised preparations of small resistance arteries showing that temperature‐ and pharmacologically induced alterations in vascular tone can evoke substantial changes in blood flow in the absence of a heart are compatible with this notion (Duling & Berne, 1970; Ellsworth et al., 1995; Jones & Berne, 1964).…”
Section: Discussionmentioning
confidence: 97%
“…This concept is in line with the findings from previous studies demonstrating that elevations in blood temperature are strongly associated with rises in red cell deformability and dispersion (Çinar et al., 2001; Manteuffel‐Szoege, 1960, 1969; Pinho et al., 2016) and reductions in blood viscosity and frictional resistance (Snyder, 1971; Çinar et al., 2001; Lim et al., 2010; Shin et al., 2004), although an increased blood viscosity has also been reported with acute whole‐body hyperthermia in humans (Gibbons et al., 2020). Notably, an elegant study in the 3‐day‐old chick embryo model showed that when the heart was stopped, blood continued to flow, albeit at a lower velocity (Li & Pollack, 2023). Moreover, when infrared radiation was introduced, the post mortem blood velocity increased ∼3.7‐fold whereas blood slowed down when the infrared radiation was removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical transport mechanisms, including oxygen transport, nutrients distribution, and gas exchange facilitated by flowing liquid within vascular networks and the surrounding interstitial spaces are widely acknowledged as critical for tissue development and for shaping the overall architecture of vascular networks within tissues. 1,2 These flow processes result in the generation of varying shear stresses within multi-sized vessels, which are governed by the pulsating heart in living organisms, as investigated using models such as chick 3 , zebrafish 4 , and frog embryos. 5 Conversely, within developing vessels of engineered tissues in for instance microfluidic chips, these shear stresses are regulated by the pressure driven flows generated by micropumps.…”
Section: Introductionmentioning
confidence: 99%